2022
DOI: 10.2196/35631
|View full text |Cite
|
Sign up to set email alerts
|

Cell Phone Availability and Usage for mHealth and Intervention Delivery to Persons Living With HIV in a Low-Resource Setting: Cross-sectional Study

Abstract: Background HIV/AIDS is now a manageable chronic illness owing to effective antiretroviral therapy (ART), which involves routine follow-up care, including regular physical visits to the clinic. In the recent past, and in wake of the COVID-19 pandemic, there has been increased need for virtual care and intervention delivery, a modality known as mobile health (mHealth), which includes cell phone–delivered services for medical and public health practice. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…A vast majority of participants reported having access to mobile phones (98.0%), indicating potential feasibility for utilizing mobile health (mHealth) interventions such as text messaging for HIV-related communication. These findings align with and reinforce the insights gleaned from previous research conducted in resource-limited setting (23)(24)(25)(26)(27). The studies have consistently demonstrated the extensive use of mobile phones even in regions with limited access to traditional healthcare infrastructure.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A vast majority of participants reported having access to mobile phones (98.0%), indicating potential feasibility for utilizing mobile health (mHealth) interventions such as text messaging for HIV-related communication. These findings align with and reinforce the insights gleaned from previous research conducted in resource-limited setting (23)(24)(25)(26)(27). The studies have consistently demonstrated the extensive use of mobile phones even in regions with limited access to traditional healthcare infrastructure.…”
Section: Discussionsupporting
confidence: 86%
“…mHealth) interventions such as text messaging for HIV-related communication. These findings align with and reinforce the insights gleaned from previous research conducted in resource-limited setting(23)(24)(25)(26)(27). The studies have consistently demonstrated the extensive use of mobile phones even in regions with limited access to traditional healthcare infrastructure.The ubiquity of mobile phones in such setting has been pivotal in reaching remote and underserved populations with healthcare information and services.Regarding the comfortability in engaging with HIV counseling services, participants who reported receiving HIV-related text messages in the past were more likely to feelcomfortable talking to a HIV counselor on the National HIV Hotline following HIVST.…”
supporting
confidence: 86%
“…Access to mobile phones is expected to be lower among people with TB than in the general population (18% vs. 7.8% in Peru from 2007-2013) (12). Mobile phone access among populations affected by TB in Uganda has been reported to be high (89% among PLHIV with latent TB in a cohort in western Uganda (12) and 58% ownership with an additional 42% indirect access among household contacts of people with TB in urban Kampala (13). Nevertheless, an intervention that relies on cellphone access systematically excludes some of the most vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Low enrollment has been a challenge in previous studies of 99DOTS and other cellphone-based DATs, raising concerns about equity and access to this mode of care. Access to mobile phones is expected to be lower among people with TB than in the general population (18% vs. 7.8% in Peru from 2007-2013) (12). Mobile phone access among populations affected by TB in Uganda has been reported to be high (89% among PLHIV with latent TB in a cohort in western Uganda (12) and 58% ownership with an additional 42% indirect access among household contacts of people with TB in urban Kampala (13).…”
Section: Discussionmentioning
confidence: 99%